2016
DOI: 10.1530/rep-16-0154
|View full text |Cite
|
Sign up to set email alerts
|

Uterine flushing proteome of the tammar wallaby after reactivation from diapause

Abstract: The marsupial tammar wallaby has the longest period of embryonic diapause of any mammal, up to 11 months, during which there is no cell division or blastocyst growth. Since the blastocyst in diapause is surrounded by acellular coats, the signals that maintain or terminate diapause involve factors that reside in uterine secretions. The nature of such factors remains to be resolved. In this study, uterine flushings (UFs) were used to assess changes in uterine secretions of tammars using liquid chromatography-mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Data from different published studies in various species was used to gain insight into potentially important factors for the regulation of diapause and reactivation of embryo development in the roe deer. The total number of 819 identified and quantified uterine fluid proteins falls within the observed range (between 299 and 1359) in various species including cows, mouse, pig and horse (Kayser et al 2006, Mullen et al 2012, Forde et al 2014, 2015, Jalali et al 2015, Kelleher et al 2016, Martin et al 2016, Smits et al 2018).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Data from different published studies in various species was used to gain insight into potentially important factors for the regulation of diapause and reactivation of embryo development in the roe deer. The total number of 819 identified and quantified uterine fluid proteins falls within the observed range (between 299 and 1359) in various species including cows, mouse, pig and horse (Kayser et al 2006, Mullen et al 2012, Forde et al 2014, 2015, Jalali et al 2015, Kelleher et al 2016, Martin et al 2016, Smits et al 2018).…”
Section: Discussionmentioning
confidence: 63%
“…In cattle, pigs or mice, none of these proteins has been reported to show a rise prior to implantation as observed in roe deer. Supported by the findings in tammar wallaby (Martin et al 2016), roe deer embryo development may be reactivated by the presence of positive regulators of the cell cycle. In the tammar wallaby, the high abundance of cell cycle inhibition proteins during diapause switches to increased abundance of growth factors once the embryo resumes development (Martin et al 2016).…”
Section: Discussionmentioning
confidence: 87%
“…The CDKN1A cell cycle inhibition pathway might also play a role in inducing mitotic arrest during diapause at the G0 or G1 phase of the cell cycle (reviewed by Lopes et al, 2004). In support of this, it has been shown that uterine secretory proteins of the CDKN1A cell cycle inhibition pathway, which have the potential to induce arrest of the blastocyst in G0 , are present in the uterine fluid of the tammar during diapause (Martin et al, 2016), although further studies are needed to confirm this possibility. MicroRNAS are also likely to be involved since, in the mouse, at least 45 microRNAs are differentially expressed between embryonic diapause and reactivation, 38 of which are downregulated at reactivation (Liu et al, 2012).…”
Section: Downstream Effects On Blastocysts and Stem Cellsmentioning
confidence: 98%
“…More recently, HB-EGF and ERBB4 have been detected in the uterus and blastocyst of both the tammar and mink specifically at reactivation from diapause, distinct from implantation . In addition, it has been shown that the soluble form of epidermal growth factor receptor (EGFR), which can also bind to HB-EGF, and another mitogen, hepatoma-derived growth factor (HDGF), are present in the tammar uterine fluid from d3 until at least d11 after removal of pouch young (RPY, equivalent to days of reactivation), when these secreted proteins constitute 21% of the uterine fluid proteome (Martin et al, 2016). Together, these findings suggest that reciprocal EGF family signalling between the endometrium and embryo is likely to play a central role in reactivation from diapause.…”
Section: Growth Factors and Cytokines In The Uterine Environmentmentioning
confidence: 99%
See 1 more Smart Citation